The Role of Content Marketing, FoMo, Social Influencer, and Flash Sale on Gen Z Impulse Buying in Semarang Regency on the TikTok Marketplace - Savitri, Sherly Dwi Ditzi; Widyaningsih, Dewi; Andriana, Myra (Ekspektra : Jurnal Bisnis dan Manajemen, 2025)
This study aimed to investigate the role of content marketing, FoMo (Fear of Missing Out), social influence, and flash sale on impulse buying among Gen Z consumers in Semarang Regency on the TikTok Marketplace. Utilizing an explanatory research design, a purposive sampling technique was employed to select 96 valid and reliable Gen Z participants from Semarang Regency. Data were collected via a questionnaire distributed through Google Forms, and multiple linear regression analysis was applied for data analysis. The findings indicated that content marketing and social influence did not individually affect impulse buying. Conversely, FoMo and flash sales were found to have a positive and significant impact on impulse buying. Furthermore, the combined influence of all independent variables on impulse buying was significant. This research concludes that while some digital marketing strategies may not directly trigger impulse purchases, urgency- and scarcity-driven tactics are highly effective for Gen Z on TikTok. The study's implications suggest that marketers should prioritize leveraging FoMo and flash sales to drive immediate consumer action on social commerce platforms.